Peningkatan Hasil Belajar Siswa dalam Pembelajaran Tematik Terpadu dengan Model Problem Based Learning di Sekolah Dasar - Guciano, Akbar; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
Abstract : Improvement of student learning outcomes in integrated thematic learning with problem based learning models in primary schools. The purpose of this study is to improve student learning outcomes in integrated thematic learning with Problem Based Learning models in grade V elementary school. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. The subjects of this study were 25 teachers and Grade V students. The study was conducted in two cycles. Research procedures include, planning, implementing, observing, and reflecting. The results of the research show that: a) The average RPP of the first cycle is 81.77% (Good) and the second cycle is 97.72% (Very Good) b) The average implementation on the aspects of the first cycle teacher 87.49% (Good) and Cycle II 95.83% (Very Good) c) Average Implementation of the aspects of students Cycle I 79.16% (Enough) and Cycle II 95.83% (Very Good) d) The average student learning outcomes in Cycle I 77.73% (Enough) and Cycle II 88.59 (Good). Thus the Cooperative Model Type Picture and Picture can improve the Integrated Thematic learning outcomes of fifth grade students of SDN 10 Sapiran Bukittinggi city